Treatment and utilization of wastes - Malaysia's experiences - Megat Mohd Noor, Megat Johari; Sham Baharin, Badlishah (1986)
Wastes are useful resources which are not being utilized. It can however be detrimental to life when left untreated or ignored. Direct or indirect utilization of waste will not only help to control pollution but also an added income.This paper intend to highlight some areas of R and D utilizing microbial degradation being undertaken. Three types of wastes have been identified namely from the agro-based industry, municipality and manufacturing industry.Current treatment technologies and utilizatiion of the by products are also being included.